STUDI TENTANG PENGARUH PEMBELAJARAN PPKN TERHADAP PARTISIPASI PEMILIH PEMULA PADA PILKADA ROKAN HILIR TAHUN 2020 DI SMAN 1 PUJUD - Rusmayanti, Desi; Eddison, Ahmad; Primahardani, Indra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by a phenomenon that appears based onpre-research that has been carried out by previous researchers and is in accordancewith the conditions in the field which shows the level and influence of PPKn learning onbeginner voter participation. The formulation of the problem in this study is how theinfluence of Civics learning on beginner voter participation in the 2020 Rokan HilirElections participants at SMAN 1 Pujud. The purpose of this study was to find out howthe effect of PPKn learning on beginner voter participation in the 2020 Rokan HilirElections at SMAN 1 Pujud. This research uses method is descriptive quantitative, datacollection instrumentusing a quastionnaire consisting of 24 statement. The populationin this study were all novice voters at SMAN 1 Pujud as many as 70 with a sample of50% of the total population to 35 respondents using the Random Sampling Technique.Based on the result of the study, there is a positive ifluence between PPKn learning onbeginner voter participation. This can be proven by linear regressionanalysis using theSPSS application namely Y = -12,164 + 1,031X.The result of the above equation can betranslate as a constant of -12,164 which means that the value of consistency of thePPKn learning is -12,164, the regression coefficient of X is 1,031 whivh states that theaddition of 1% of the value of the PPKn learning, the beginner voters will increase by1,031. This coeficcient is positive, meaning that the PPKn learning (X) on beginnervoter (Y) has a positive effect.Key Words: Influence Study, PPKn learning, Beginner Voters Participation